2011
DOI: 10.1021/ar2001952
|View full text |Cite
|
Sign up to set email alerts
|

π-Conjugated Cyanostilbene Derivatives: A Unique Self-Assembly Motif for Molecular Nanostructures with Enhanced Emission and Transport

Abstract: π-Conjugated organic molecules represent an attractive platform for the design and fabrication of a wide range of nano- and microstructures for use in organic optoelectronics. The desirable optical and electrical properties of π-conjugated molecules for these applications depend on their primary molecular structure and their intermolecular interactions such as molecular packing or ordering in the condensed states. Because of the difficulty in satisfying these rigorous structural requirements for photoluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
469
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 693 publications
(477 citation statements)
references
References 32 publications
7
469
0
1
Order By: Relevance
“…[25,35] Advances at the level of the theoretical description are summarized by Gierschner and Park in Ref. [36].…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[25,35] Advances at the level of the theoretical description are summarized by Gierschner and Park in Ref. [36].…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Substitution of π-conjugated systems with bulky side groups that hinder π-π cofacial stacking prevents aggregation-induced quenching, especially in the case of H-aggregation. Recently, restriction of intramolecular rotation and conformational planarization mechanisms was proposed as a chemical design strategy toward the generation of highly luminescent organic solids in which aggregation-induced emission (AIE) [9,10] or aggregation-induced enhanced emission (AIEE) [11] phenomena operate. In the case of BF2 complexes of 2'-hydroxychalcones and curcuminoids, we showed that NIR emission property is characteristic of tightly packed chromophores experiencing strong excitonic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…This AIE phenomenon can be explained by the restriction of non-radiative vibrational relaxation processes in the aggregated solid state. Representative examples of AIE-active fluorophores include siloles, [6][7][8][9] cyanostilbenes, [10][11][12] o-carborane derivatives [13][14][15][16][17] and tetraphenylethenes [18][19][20][21][22][23] . Some of these fluorophores have proved useful as non-doped emission layers in fluorescent OLEDs.…”
Section: Introductionmentioning
confidence: 99%